Interactive neurotoxicity of environmentally relevant concentrations of polystyrene nanoplastics and butyl methoxydibenzoyl methane on early zebrafish embryos - Zhou, Ranran; Yang, Haohan; Zhou, Dao; Yang, Shixin; Shi, Zhiqiao; Jin, Qijie; Ding, Zhuhong (Frontiers in Marine Science, 2022)
Organic ultraviolet filters (OUVFs) and nanoplastics (NPs) are two important new pollutants that coexist widely in freshwater and coastal habitats. Both OUVFs and MPs can be taken up by aquatic organisms and may be toxic or co-toxic. In this study, the neurotoxicity and interaction neurotoxicity of the typical OUVFs butyl methoxydibenzoyl methane (BM-DBM) and polystyrene nanoplastics (PS-NPs) on zebrafish at environmental concentrations were comprehensively investigated at the tissue and molecular levels using transgenic or non-transgenic zebrafish. Results showed that both BM-DBM and PS-NPs induced abnormal expression of developmental genes neurogenin 1, glial fibrillary acidic protein, Finkel-Biskis-Jinkins osteosarcoma oncogene, growth-associated protein 43, synapsin IIa, and apoptosis regulator a (Bcl2a), Bcl2 associated x and apoptosis-related cysteine peptidase a, neuronal loss, motor neuron axon deletion, neuronal apoptosis and behavioral abnormalities in larvae thus being neurotoxic. BM-DBM also specifically interferes with neurotransmitter systems and affects signaling between neurons. In addition, PS-NPs and BM-BDM exerted synergistic and antagonistic effects in inducing apoptosis in neuronal cells and developmental neurotoxicity, respectively. Our results highlight the neurotoxic risk of PS-NPs and BM-BDM and the complex interactive neurotoxic effects of the two. We anticipate that our study may lay the foundation for ecological risk assessment of OUVFs and PS-NPs and exploration of complex interactions between PS-NPs and hydrophobic organic pollutants.